Psychosexual Well-Being in Adults With and Without Autism Spectrum Disorder. - Rocha, Jessica N. (Tufts University. Tisch Library., 2020)
Sexual well-being is vital to healthy development and life satisfaction. Unfortunately, individuals with Autism Spectrum Disorder (ASD) are severely overlooked when it comes to their sexuality and sexual well-being. ASD is a developmental condition that impacts and creates challenges in social interactions, verbal and nonverbal communication, and can present with repetitive or fixated behaviors and interests. The communication and social difficulties autistic individuals experience lead to unsatisfactory interpersonal relationships and an inability to be sexually expressive, which can lead to low self-esteem and a lowered quality of life. Psychosexual Well-Being is a working model that I proposed, aimed at exploring how an individual's intrapersonal relationship affects their sexual well-being. It is comprised of sexual self-concept, sexual knowledge, and sexual feelings and attitudes. Using anonymous self-report survey measures that concentrate more on the individual's introspective orientation towards sexuality rather than past sexual encounters and behavior, I sought to understand the foundation of sexual expression and sexual behavior. Furthermore, by comparing groups based off of diagnostic criteria of Autism Spectrum Disorder (ASD) and neurotypical (NT), this study aimed to explore how the sexuality and sexual identity of autistic individuals may differ from the neurotypical population.; Poster presented at the Tufts Graduate Student Council's 24th Graduate Student Research Symposium, March 6, 2020. 1st place winner.